Comparison of Learning Outcomes Head Stand Through Application of the Methoddrill And Methodsdiscoveri Learning In Class VIII Students of SMP Negeri 67 Central Maluku - Rey, Yuliana; Fenanlampir, Albertus; Matitaputty, Johanna (International Journal of Education, Information Technology, and Others, 2024)
This research is comparative research, namely research that is comparative in nature. The variable studied is the comparison of Kopstand learning outcomes through the application of the Drill Method and the Discovery Learning Method in Class VIII Students of SMP Negeri 67 Central Maluku, totaling 21 students. Data sources come from teachers, students and researchers. Data collection techniques are observation, tests, and documentation or archives. From the research results obtained, the majority obtained scores with Very Good criteria (89-100), namely the learning outcomes using the Drill method amounted to 0 students and the learning outcomes using the Discovery Learning method amounted to 0 students according to these criteria. It is explained in figure 4.6. For the Good criteria (77-88) for the learning outcomes using the Drill learning method, there were 9 students who got this score and for the learning outcomes using the Discovery Learning learning method there were 8 students who obtained these criteria. Meanwhile, the criteria for Sufficient (65-76) for the Drill learning method are 10 students and the Discovery Learning learning method is 10 students. Meanwhile (<=64) for the Drill method there were only 2 students and for the Discovery Learning method there were 3 student